STUDENTS’ BACKGROUND IN MATHEMATICS: THE CAUSES OF NEGATIVE TRENDS - Vera I. Toktarova; Svetlana N. Fedorova (Высшее образование в России)
Abstract. The article focuses on the essential problem of Russian higher education – the need of high level of students’ background in mathematics in order to accomplish long-term goals of socioBeconomic innovation development. Due to this problem the analysis of the quality of students’ mathematical training in higher educational institutions is provided, the tendency of decreasing of its level is designated, the reasons of this fact are considered. Theoretical and empirical research methods were used in the study. The authors consider the results of students questioning to determine the significance of mathematics learning problems; they specify the quality of mathematical training of Russian schoolchildren according to the mathematical results of the USE, an international TIMSS and PISA researches.